Developing bacterial set box media containing fiqh al biah for Islamic senior high school - Uswatul Wadhichatis Saniyyah; Nur Hayati; Saifullah Hidayat (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
The limitations of bacterial visualization media make bacteria consider as abstract and difficult material to study. Furthermore, the implementation of bacteria material and the integration of Islamic values are difficult to teach. This research aimed at developing and validating the BSB (Bacterial Set Box) media containing fiqh al biah. The method used in this research was R&D (Research and Development) with 4D model (Define, Design, Develop, and Disseminate) by Thiagarajan et al. The media developed was three dimensions (3D), which was packed up in a box which contained three packages. The first box was bacterial visualization; the second box was bacterial classification; the third box was 3D box containing fiqh al biah. The field test was carried out in Al Azhar Islamic Public School 16 and MA Nurussalam Semarang. The results showed that the validation percentages were 94% (material expert), 79% (media expert), 96% (integration expert), 92% (biology teacher of Al Azhar Islamic Public School 16), and 86% (biology teacher of MA Nurussalam). A pilot scale test and a large-scale test showed very feasible. It can be concluded that BSB media containing fiqh al biah is very feasible to use.